“Milking the lions”: An analysis of conservation performance payments in eastern and southern Africa - Joseph Hamm; George Holmes; Mathew Bukhi Mabele; Julia Martin‐Ortega (Conservation Science and Practice)
Abstract Conservation performance payments (CPPs) aim to encourage coexistence between humans and large carnivores by tying payments to species presence or abundance. While there is growing interest in the development of these programs, they remain the subject of little empirical research. Furthermore, there is no literature on CPPs for carnivores in Africa, despite the continent's global importance in carnivore conservation and the fact that multiple such schemes are currently in operation. This research establishes where and how these schemes function and identifies recurring challenges associated with their implementation. We conducted semi‐structured interviews with representatives of nine conservation performance payment programs operating across five countries in eastern and southern Africa. We find that despite their theoretical simplicity, local complexities, and pragmatism mean there is significant variation in how CPPs operate. This includes differences in monitoring methods, governance, and all aspects of payments. The inclusion of input conditionality (i.e., fines or bonuses for certain actions) in a majority of schemes also challenges the prevailing conceptualization of CPPs as entirely results‐based. Recurring challenges include securing long‐term funding, setting suitable payment levels, and ensuring equitable governance. Practitioners view performance payments as a promising approach for carnivore conservation, but their roll‐out risks moving faster than our understanding of them.